Pharmacological blockade of either cannabinoid CB1 or CB2 receptors prevents both cocaine-induced conditioned locomotion and cocaine-induced reduction of cell proliferation in the hippocampus of adult male rat - BLANCO-CALVO, EDUARDO; RIVERA, PATRICIA; ARRABAL, SERGIO; VARGAS, ANTONIO; PAVON, FRANCISCO JAVIER; SERRANO, ANTONIA; GALEANO, PABLO; RUBIO, LETICIA; SUAREZ, JUAN; RODRIGUEZ DE FONSECA, FERNANDO (Frontiers in Integrative Neuroscience, 2014)
Addiction to major drugs of abuse, such as cocaine, has recently been linked to alterations in adult neurogenesis in the hippocampus. The endogenous cannabinoid system modulates this proliferative response as demonstrated by the finding that pharmacological activation/blockade of cannabinoid CB1 and CB2 receptors not only modulates neurogenesis but also modulates cell death in the brain. In the present study, we evaluated whether the endogenous cannabinoid system affects cocaine-induced alterations in cell proliferation. To this end, we examined whether pharmacological blockade of either CB1 (Rimonabant, 3 mg/kg) or CB2 receptors (AM630, 3 mg/kg) would affect cell proliferation [the cells were labeled with 5-bromo-2′-deoxyuridine (BrdU)] in the subventricular zone (SVZ) of the lateral ventricle and the dentate subgranular zone (SGZ). Additionally, we measured cell apoptosis (as monitored by the expression of cleaved caspase-3) and glial activation [by analyzing the expression of glial fibrillary acidic protein (GFAP) and Iba-1] in the striatum and hippocampus during acute and repeated (4 days) cocaine administration (20 mg/kg). The results showed that acute cocaine exposure decreased the number of BrdU-immunoreactive (ir) cells in the SVZ and SGZ. In contrast, repeated cocaine exposure reduced the number of BrdU-ir cells only in the SVZ. Both acute and repeated cocaine exposure increased the number of cleaved caspase-3-, GFAP- and Iba1-ir cells in the hippocampus, and this effect was counteracted by AM630 or Rimonabant, which increased the number of BrdU-, GFAP-, and Iba1-ir cells in the hippocampus. These results indicate that the changes in neurogenic, apoptotic and gliotic processes that were produced by repeated cocaine administration were normalized by pharmacological blockade of CB1 and CB2. The restorative effects of cannabinoid receptor blockade on hippocampal cell proliferation were associated with the prevention of the induction of conditioned locomotion but not with the prevention of cocaine-induced sensitization.